Defect and Doping Co-Engineered Non-Metal Nanocarbon ORR Electrocatalyst - Zhang, Jian; Zhang, Jingjing; He, Feng; Chen, Yijun; Zhu, Jiawei; Wang, Deli; Mu, Shichun; Yang, Hui Ying (Nano-Micro Letters, 2021)
Exploring low-cost and earth-abundant oxygen reduction reaction (ORR) electrocatalyst is essential for fuel cells and metal–air batteries. Among them, non-metal nanocarbon with multiple advantages of low cost, abundance, high conductivity, good durability, and competitive activity has attracted intense interest in recent years. The enhanced ORR activities of the nanocarbons are normally thought to originate from heteroatom (e.g., N, B, P, or S) doping or various induced defects. However, in practice, carbon-based materials usually contain both dopants and defects. In this regard, in terms of the co-engineering of heteroatom doping and defect inducing, we present an overview of recent advances in developing non-metal carbon-based electrocatalysts for the ORR. The characteristics, ORR performance, and the related mechanism of these functionalized nanocarbons by heteroatom doping, defect inducing, and in particular their synergistic promotion effect are emphatically analyzed and discussed. Finally, the current issues and perspectives in developing carbon-based electrocatalysts from both of heteroatom doping and defect engineering are proposed. This review will be beneficial for the rational design and manufacturing of highly efficient carbon-based materials for electrocatalysis. Highlights: 1 Recent advances of non-metal nanocarbon materials for electrocatalytic oxygen reduction reaction (ORR) are comprehensively summarized in terms of co-engineering of heteroatom doping and defect inducing. 2 The characteristics, ORR performance, and the related mechanism of non-metal nanocarbon are emphatically analyzed and discussed. 3 The current issues and perspectives in developing carbon-based electrocatalysts from both of heteroatom doping and defect engineering are pointed out and proposed.